Investigation of structural and optical properties of graphene oxide-coated neodymium nanoparticles doped zinc-tellurite glass for glass fiber - Muhammad Noorazlan Abd Azis (Tanjung Malim, 2021)
Investigation of structural and optical properties of graphene oxide-coated neodymium nanoparticles doped zinc-tellurite glass for glass fiber by Muhammad Noorazlan Abd Azis